Elimination of naturally occurring crosslinks in vaccinia virus DNA after viral penetration into cells. - Pogo, B G (1977)
Vaccinia virus DNA, extracted from purified virus or from the cytoplasmic fraction of virus-infected cells very shortly after infection, was analyzed by sedimentation in alkaline and neutral sucrose gradients. The sedimentation properties of vaccinia DNA under denaturing conditions changed, immediately after penetration into the cell, from the characteristic circular viral DNA (crosslinked double-stranded linear DNA) to nicked circular DNA or to single-stranded molecules. This transition occurred at the time of uncoating of the virus and with a slight change in the DNA size, as judged by sedimentation in neutral sucrose. These results indicate that the crosslinks, that held the complementary strands of the genome together, are removed after penetration. When vaccinia DNA was incubated with the supernatant fraction of virus-infected cells, a similar change in the sedimentation properties of the DNA under denaturing conditions was observed. It is concluded that the endonuclease present in the supernatant of infected cells eliminated the crosslinks in the DNA, and that this enzymatic hydrolysis may be the mechanism by which crosslinks are removed prior to DNA replication.